Production of rutile titanium dioxide nanoparticles by trans-ferulic acid and their biomedical applications. (December 2022) - Chahardoli, Azam; Hosseinzadeh, Leila; Shokoohinia, Yalda; Fattahi, Ali
Abstract: Titanium dioxide nanoparticles (TiO2 NPs) are popular materials with high annual production and increasing applications in different fields. In the current research, we synthesized TiO2 NPs with the help of the reducing potential of trans-ferulic acid (FA). FA-TiO2 NPs are principally characterized by X-Ray Diffraction (XRD), Fourier Transform-Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Field-Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive X-Ray Analysis (EDX), and Thermogravimetric (TGA) techniques. Then, their biomedical properties were investigated by in vitro hemolysis, anti-inflammatory, and cytotoxicity tests. According to physiochemical analysis, FA-TiO2 NPs had mostly rod-shaped morphology with a rutile crystallographic phase. These NPs were non-hemolytic with high anti-denaturation and membrane stabilization activity and thus excellent in vitro anti-inflammatory effects. FA-TiO2 NPs decreased the cell viability of A375 (melanoma cell line), MCF-7 (breast cancer cell line), and human skin fibroblast (normal cell line) in a dose-dependent manner. The IC50 values of FA-TiO2 NPs were above 12.5, 25, and 50 µg/mL against A375, MCF-7, and skin fibroblast cell lines, respectively. In this study, we demonstrated the biocompatibility and valuable potential of FA-TiO2 NPs in biomedical applications. Graphical Abstract: ga1